Astrometric study of Gaia DR2 stars for interstellar communication. Issue 4 (17th August 2020) - Seto, Naoki; Kashiyama, Kazumi
Abstract: We discuss the prospects of high precision pointing of our transmitter to habitable planets around Galactic main sequence stars. For an efficient signal delivery, the future sky positions of the host stars should be appropriately extrapolated with accuracy better than the beam opening angle Θ of the transmitter. Using the latest data release (DR2) of Gaia, we estimate the accuracy of the extrapolations individually for 4.7 × 10 7 FGK stars, and find that the total number of targets could be 10 7 for the accuracy goal better than 1″. Considering the pairwise nature of communication, our study would be instructive also for SETI (Search for Extraterrestrial Intelligence), not only for sending signals outward.